Looming deprofessionalization: State interventions into the operation of professional institutions of secondary teacher training in Hungary in the early twenties - Garai, Imre (Historia y Memoria de la Educación, 2023)
In the paper, the transformation processes of secondary teacher training in Hungary are examined through the investigation of personal and conceptual changes related to two professional institutions, namely the Secondary Teacher Training Institution and the Secondary Teacher Examination Committee in Hungary in the early 1920s. By employing the method of document analysis of archival sources, substantial amount of primary sources were involved in the research from various archives. Additionally, the secondary literature review is also used as a research method in contextualizing the findings of the analysis. As for the interpretation, notions related to the critical approach of professionalization theories are applied in the paper. The study gives a brief overview of the development of professional institutions from the mid of the nineteenth century to 1919 in order to provide an insight into some of the main barriers of their development, which expected to be solved by the new regime in Hungary solidified after 1920. The appointment of new leadership in the teacher training institution, the influence on its curriculum, the forced interrogation of the political views of teacher candidates delegated to the teacher examination committee before the state examination and the determination of the reform of the teacher examination regulations all suggest that the state intention of reshaping the teacher training according to circumstances of the new political-social reality after the war resulted in a new relationship between the state and the professional institutions that could lead to deprofessionalization on the long term. This development could be regarded as an unprecedent phenomenon compared to the situation of professionals in other countries in the Central and Eastern European region.